A CPW-fed Triple-band Antenna for WLAN and WiMAX Applications - Yang, Xiaolin; Kong, Fangling; Liu, Xuelin; Song, Chunyan (Společnost pro radioelektronické inženýrství, 2014)
In this letter, a compact printed antenna fed by coplanar waveguide for triple-band is presented. The proposed antenna consists of two rectangular metallic loops in front and a slit square ring on the backside. Tri-band has been achieved, which can be easily tuned by adjusting the sizes of the rectangles. An analysis of equal lumped circuit mechanism as well the triple band operation is provided. Key parameters to tune the resonant frequencies have been identified. The overall dimension of the proposed antenna is 30×26 mm^2. Simulated results show that the presented antenna can cover three separated impedance bandwidths of ～13% at 300 MHz (2.2–2.5 GHz), ～14% at 500 MHz (3.3–3.8 GHz), and ～15% at 800 MHz (5.1–5.9 GHz), which are well applied for both 2.4/5.2/5.8-GHz WLAN bands and 3.5/5.5-GHz WiMAX bands.
Keywords: Triple-band; coplanar waveguide; equivalent circuit.